Women, welfare and the nurturing of Afrikaner nationalism : a social history of the Afrikaanse Christelike Vroue Vereniging, c.1870-1939 - Du Toit, Marijke (Department of Historical Studies, 2017)
This thesis focuses on the Afrikaans Christian Women's Organisation (ACVV), placed within the context of Afrikaner nationalist activity, and traces the variety of ways in which white, Afrikaans, middle-class women sought to construct a racially exclusive 'Afrikaner' people. Stereotypical portrayals of Afrikaner women as passive followers of an ideology constructed by men are challenged. The gendered construction of nationalism is initially examined by tracing the transition from a religious, evangelical, late nineteenth century gender discourse to an increasingly explicit Afrikaner nationalist discourse in the early twentieth century. The ACVV participated in the construction of a popular Afrikaner nationalist culture that portrayed Afrikaans women as mothers of the people or volksmoeders. The first ACVV leaders were acutely aware of the 'New Women' who abandoned conventional notions of femininity - they tried to construct a public, political identity for Afrikaans women that met the challenges of the 'modern' world, yet remained true to Afrikaner 'tradition'. The ACVV sought to fashion Afrikaans whites into 'Afrikaners' through philanthropic activity. At first, this was especially true of rural branches, but from the early 1920s, Cape Town's ACVV also responded to the growing influx of 'poor whites' by focusing specifically on social welfare work. One particular concern was the danger that women working together with blacks posed for the volk. Research on the ACVV's philanthropy is complemented by a study of the lives of landless and impoverished whites in the Cape countryside and Cape Town. Archival material and 'life history' interviews are used to explore the working lives of white, Afrikaans-speaking women who moved from rural areas to Cape Town during the 1920s and 1930s. Complex and contradictory strands made up the private and political lives of female Afrikaner nationalists. During the 1920s, they sought to create a political role for themselves by constructing a 'maternalist', nationalist discourse that articulated the notion of separate spheres for men and women -but extended vrouesake (women's issues). In many ways these were conservative women - yet they adjusted, even challenged, conventional gender roles in Afrikaans communities. In the 1930s, the four provincial Afrikaans women's welfare organisations sought to shape state-subsidised social welfare programmes. The ACVV and its sister organisations had increasingly fraught dealings with Afrikaner nationalist men in the state and church. who did not share the women's vision of female leadership in social welfare policy.